EFFORTS TO EMPOWER THE SUKARARA WEAVER COMMUNITY OF JONGGAT DISTRICT, CENTRAL LOMBOK DISTRICT IN IMPROVING THE FAMILY ECONOMY THROUGH BUSINESS CAPITAL MANAGEMENT, LABOR, AND PROMOTION - Hidayati, Nelly; Mas'ud, M.Ag, Prof. Dr. Riduan; Mulhimmah, MH, Dr. Baiq Ratna (Universitas Pamulang, 2024)
Indonesia's economic growth is influenced by the development of MSME businesses, which is one of the country's economic development priorities. Because small businesses play a role in reducing social inequality. One effort to improve the regional economy is the production of typical Lombok weaving by the MSME industry. The decline in visitors due to the COVID-19 pandemic is a problem that clearly requires strategic steps to strengthen the weaving community through education and training to form communities/groups, namely the MEKAR and KOMIDA groups. The impact of successful economic empowerment of weaving communities is : 1) Reducing the number of poor people, 2) Developing initiatives to increase community income and human resources, 3) Increasing community awareness of family welfare, 4) Empowering family independence, 5) Building community capacity and equalizing income. Capital management carried out by the regional government provides direct company capital support to weaving producers under the control of Bank Indonesia and Bank Mandiri. However, financial managers have not mastered the basics of accounting so that the implementation of financial management is still minimal and personal management does not allow for success